2020
DOI: 10.1016/j.contraception.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Birth Control Connect: A randomized trial of an online group to disseminate contraceptive information

Abstract: Objective: We sought to test whether participation in an online group including IUD users influenced IUD-related knowledge, attitudes, and behavior among IUD non-users, as a proof-ofconcept evaluation of information dissemination for less commonly used or novel contraceptives. Study design: We conducted a blinded, randomized controlled trial on the effect of online communication with IUD users within an online program called Birth Control Connect. Participants were women age 18-45 living in the United States w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Attention is directed at the evaluation of the reliability of different sources of knowledge and at any mentions of unestablished, systemic side effects, as well as at any correlations between negative attitudes toward or experiences of the IUD and sociodemographic characteristics or levels of trust in sources of information. This is in line with research highlighting the need to study factors influencing women's contraceptive choices, including women's experiences of and attitudes toward contraceptives (16,21,62), not least due to the noted importance of informal social communication for such choices (70).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…Attention is directed at the evaluation of the reliability of different sources of knowledge and at any mentions of unestablished, systemic side effects, as well as at any correlations between negative attitudes toward or experiences of the IUD and sociodemographic characteristics or levels of trust in sources of information. This is in line with research highlighting the need to study factors influencing women's contraceptive choices, including women's experiences of and attitudes toward contraceptives (16,21,62), not least due to the noted importance of informal social communication for such choices (70).…”
Section: Introductionsupporting
confidence: 77%
“…Previous findings that social networks have importance for choices of and attitudes toward contraceptives (16,22,28,29,70), that women often use a combination of sources of information about the copper IUD (16,22), and that some women consider accounts about the IUD provided via social contacts to be more reliable than information provided by healthcare professionals (22,30,32) find some support in the present study. Those with negative attitudes and unwillingness toward future use of the copper IUD, as well as those referring to systemic side effects, reported having taken part of the information about risks associated with the IUD from healthcare providers as well as from CAM sources and other individuals to a larger degree than those not reporting negative attitudes or experiences or mentioning unestablished side effects.…”
Section: The Use and Perceived Reliability Of Informationsupporting
confidence: 53%
See 2 more Smart Citations
“…19 Studies have also shown that sharing information about long-acting reversible contraception (LARC) on social media has increased individual preferences for LARC methods. 20,21 Despite the literature demonstrating the presence and influence of contraception-and sexual health-related content on social media sites, large-scale comparison of attitudes toward individual contraceptive methods on social media has yet to be undertaken. Twitter, a social networking site with over 330 million monthly users worldwide, is an ideal platform for studying contraceptive attitudes, owing to its widespread use and influence.…”
Section: Introductionmentioning
confidence: 99%